Which way goes capitalism? : in search of adequate policies in a dramatically changing world - Daianu, Daniel (Central European University Press, 2009)
A well-known academic economist and former finance minister, at present member of the European Parliament, Daianu gives a lucid and well balanced overview of the current financial turbulences that have hit the developed economies. Strongly criticizing the excesses of neoliberal capitalism, calls for implementing necessary regulatory reforms in the financial sector and for restoration of a proper balance between the functions of the state and the market. A financial meltdown, with its very dire effects on the real economy, can be prevented by adopting proper policies and regulations.